Analysis of Acid Mining Water Management Using Active Method (Case Study: Bangko Barat KPL BB 07 PT Bukit Aam Tbk. Tanjung Enim, Sumatera Selatan) - Arisah, Feni; Pratiwi, Yuniar; Yovanda, Ridho (Contemporary Journal of Applied Sciences, 2024)
The presence of acid mine water will have a negative impact on the community and the environment so that prevention and management of acid mine water is needed by utilizing quicklime and alum which function to neutralize and precipitate acid mine water. The purpose of this study was to understand the process of managing acid mine water with the active method applied at PT Bukit Asam Tbk. The results of this study are where the stages of acid mine water management start from pumping sump water and measuring the water discharge and flowing to KPL BB 07 after that the pH of the inlet and outlet water is checked periodically for 1 month, then flowed into the water body if it meets environmental quality standards, namely with a pH of 6. The dosage of quicklime and alum used varies, depending on the water conditions in the KPL